Refining the tectonic and magmatic history of the SW Grenville Province - Strong, Jacob (My University, 2017)
The largest structural trend of the major lithotectonic boundaries in the Grenville Province is located in Ontario where all lithotectonic belts are deflected around Georgian Bay, termed the Big Bend. The thesis will explore some questions related to the formation of this structural feature such as; how the geometry of Grenville aged thrusting contributed to the Big Bend and what conditions led to the formation of the pre-Grenvillian Central Metasedimentary Belt whose geometrical shape may have controlled the development of the Big Bend. First, the geometrical properties of the major lithotectonic boundaries are explored using a three-dimensional model in SketchUp. SketchUp was designed to visualize three-dimensional 1:1 scale real-world structures in Cartesian space. By utilizing refined isotope and geologic surface boundaries accompanied with seismic surveys a three-dimensional tectonic framework of the SW Grenville Province has been constructed. The three-dimensional model of the Grenville Front, Allochthon Boundary Thrust and Central Metasedimentary Belt boundary provides a visual understanding of how the thrust geometry was superimposed from the top-down, eventually producing the Big Bend. Second, 60 new Nd isotope analyses are presented for plutonic orthogneisses from the Central Metasedimentary Belt (CMB), Grenville Province. The CMB has been identified as a back-arc aulacogen with blocks of rifted crustal basement (>1.35GaTDM) in a juvenile matrix of lavas, intrusions and supracrustal sequences (1.35GaTDM). The Grimsthorpe domain is located in the center of the CMB in Ontario and contains large batholiths that exhibit older crustal formation ages known as the Weslemkoon and Elzevir batholiths. The presented Nd isotope analyses identify domains with older crustal formation ages separated by thin salients with younger crustal formation ages inside the Weslemkoon batholith. The intricate geometry of the isotope boundaries within the Weslemkoon batholith suggest that the Laurentian crustal basement was incorporated in the rift and later broken-up by rift related transtension. Continental rift and rifted-arc settings of the Danakil Depression and Gulf of California are explored as modern analogues along with rifted continental fragments known as the Danakil block and Isla Tiburon respectively. Last, the Queensborough mafic-ultramafic complex (QC) is reviewed. The QC is located at the southern end of the Elzevir batholith. The QC was interpreted as a back-arc ophiolite based on REE ratios and MORB normalized spidergrams which were argued to be comparable to modern back-arc basalts. Upon review of the published major and trace element ratios there is a mantle component that is problematical to explain with a back-arc tectonic scenario. The geochemistry suggests that the QC could be partially derived from a mantle plume. The current tectonic models contend this part of Laurentia formed only from subduction related magmatism but based on the trace element data a plume may have been involved as well. The evidence presented supports the identification of the CMB as a failed continental rift and that the failed continental rift created an embayment in Laurentia which governed ductile deformation during Grenvillian orogenic events leading to the formation of the Big Bend.
Keywords: Precambrian Geology; Grenville Province; Central Metasedimentary Belt